A STUDY ON THE FREQUENCY RESPONSE OF A COMPOSITE PRE-STRESSED SYSTEM UNDER AN INCLINED HARMONIC LOADING - Daşdemir, Ahmet (Amasya University, 2022)
Goal for the present research is investigating the dynamic behaviors regarding forced vibration of an elastic composite body on the rigid ground for four different material designations. For this purpose, the effects of the initial stress state and frequency response parameter on the forced vibration of the model are studied. Based on the linearized theory of elasticity, the nonlinear forced vibration of composite material on the rigid ground is considered. The nonlinear governing equations are linearized and boundary-contact conditions are derived using Hamilton’s principle. Total energy functional is constructed based on the principle of the variational formulation, and then the forced vibration of elastic composite plate-strip is analyzed using the finite element method (FEM). Moreover, the numerical examples related to the influences of important problem factors on our mathematical model are given. The observations show that the selection of more soft material in the upper layers has a great potential for the structural stability of the system. For the softer upper layer relatively, the wave oscillation in the plate-strip exhibits becomes more regular. In addition, the resonance values of the system decrease with the increase of the initial compressing parameter but with the initial stretching parameter.
Keywords: Composite material; Initial stress; Finite element method; Frequency response; Forced vibration; Engineering; initial stress; forced vibration; finite element method; Mühendislik; frequency response; TA1-2040; composite material; Engineering (General). Civil engineering (General)